A novel cellulose‐derived carbon aerogel@Na2Ti3O7 composite for efficient photocatalytic degradation of methylene blue. Issue 48 (5th July 2021) - Liu, Yu; Chen, Yian; Chen, Zhishan; Qi, Haisong
Abstract: A scale‐up and sustainable method was developed to fabricate novel photocatalyst cellulose‐derived carbon aerogel@Na2 Ti3 O7 composite (CAT) by in situ growth of Na2 Ti3 O7 nanowhisker on the surfaces of fibers. With a three‐dimensional (3D) mesoporous network interconnected structure and a high specific surface area (248.92 m 2 /g), CAT exhibited excellent photocatalytic activity and methylene blue (MB) removal rate (98.3%). The photocatalytic experimental results showed that the CAT could degrade MB in the aqueous solution within 90 min. Compared with most reported catalysts, CAT exhibited a higher MB removal rate and shorter catalytic time. Therefore, the photocatalyst CAT based on environmentally friendly and low‐cost cellulose displayed great application potential in the degradation of MB. Abstract : Carbon fibers with evenly distributed Na2 Ti3 O7 nanowhisker formed a CAT with a three‐dimensional macroporous structure. During the photodegradation process, the CAT would catalyze the production of light‐induced reactants such as hydroxyl radicals (OH), holes (h+), and superoxide radicals (O2−). The generated active species O2−, h+ and OH degrade the MB dye molecules to CO2, H2 O or other products. Compared with most reported catalysts, CAT exhibited a higher MB removal rate and a shorter catalytic time.